Kajian Pengolahan Limbah Cair Domestik di PT. X - Farhan Auladana Putra Anhar; Yayok Suryo Purnomo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
PT X is one of the industries located in East Java that produces liquid waste. The industrial sector is indeed a large producer of liquid waste. One of the liquid wastes produced is domestic liquid waste. The industry has the responsibility to manage domestic liquid waste in accordance with Government Regulation Number 22 of 2021 which requires industries to carry out domestic wastewater management before being discharged into water bodies. One of the efforts made by the industry to manage the domestic wastewater produced is to use a Domestic Wastewater Treatment Plant. The quality of the treated water has met the domestic wastewater quality standards to be discharged into river and does not pollute the environment.